Genetic variability, correlation and path analysis for selection in elite breeding material of sesame (Sesamum indicum L.): GENETIC VARIABILITY, CORRELATION AND PATH ANALYSIS IN BREEDING MATERIAL OF SESAME - ALPANA KUMARI SINGH,; SIMA SINHA,; SATYENDRA,; SWETA SINHA,; DINKAR,; P K SINGH, (Journal of Oilseeds Research, 2024)
Sesame is an oilseed crop with chromosome number 2n=26 belonging to the family Pedaliaceae. Although itis a potent crop, yet its yield is not at par with other oilseeds. Its indeterminate growth habit and seed shattering due to non-synchronous maturity are the major causes of its low yield. Focusing on this problem research was designed to study the various morphological traits related to the crop and their inter-relationship with yield. Twenty-nine sesame genotypesincluding three checks, two national checks (GT-10, TKG-22) and one zonal check (JTS-08) from different sources were planted in Randomized Block Design with three replications and data were collected on 14 quantitative characters. All the genotypes have significant variance for all the character under study. Two characters flowering period and growth during flowering was used to classify the genotypes determinate, semi-determinate and indeterminate. RT-103, BRT-10-01 comes under determinate, 11 under semi-determinate and 3 under indeterminate were found. High heritability coupled with high genetic advance was observed for flowering period, number of primary branches, seed per capsule, capsule length, indicating that heritability is mainly due to additive gene action and selection for these traits would be more effective. Further correlation studies revealed positive significant correlation with number of primary branches, number of capsules per plant, seed per capsule thereby direct selection of these traits may lead to increase in genetic potential of seed yield. High positive direct effect of seed per capsule on yield per plant and some other traits shown high positive indirect effect on seed yield. Hence, these characters should be given preference during selection.